Wet Chemical Synthesis of Non-solvated Rod-Like α'-AlH3 as a Hydrogen Storage Material - Liu, Haizhen; Ma, Hongyu; Zhang, Longfei; Gao, Shichao; Wang, Xinhua; Xu, Li; Liu, Shuangyu; Huang, Xiantun; Lu, Chenglin; Luo, Hui; Ning, Hua; Lan, Zhiqiang; et al. (Frontiers in Chemistry, 2020)
Aluminum hydride (AlH3) is a promising candidate for hydrogen storage due to its high hydrogen density of 10 wt%. Several polymorphs of AlH3 (e.g., α, β, and γ) have been successfully synthesized by wet chemical reaction of LiAlH4 and AlCl3 in the ether solution followed by desolvation. However, the synthesis process of α'-AlH3 by wet chemical still remain unclear. In the present work, α'-AlH3 was synthesized by first formation of the etherate AlH3 through a reaction of LiAlH4 and AlCl3 in the ether solution. Then the etherate AlH3 was heated at 60 °C under ether gas atmosphere and in the presence of excess LiAlH4 to remove the ether ligand. Finally, α'-AlH3 was obtained by ether washing of the excess LiAlH4. It was suggested that the desolvation of the etherate AlH3 under ether gas atmosphere is essential to the formation of α'-AlH3 from the etherate AlH3. The as-synthesized α'-AlH3 are rod-like particles and can release hydrogen of 7.7 wt% in the temperature range 120−200°C.